Literature Review Pijat Punggung untuk Mengurangi Nyeri Persalinan Kala I - Hidayati, Ulfah (Jurnal Komunikasi Kesehatan, 2024)
First stage labor is often associated with pain due to uterine contractions, dilation and effacement of the cervix. This article aims to determine whether back massage can reduce first stage labor pain. The article was written using a literature review method using electronic databases, namely PubMed and ScieneDirect with the keywords "back massage", "labor", and "pain", then the articles were selected using inclusion and exclusion criteria. The search results using keywords, PubMed contained 10 articles and ScieneDirect contained 3812 articles. Then the articles were selected based on the inclusion and exclusion criteria that had been determined in 2 electronic databases. The screening results obtained 6 articles containing back massage, warm back massage, and back massage using lavender essential oil can reduce first stage labor pain. From the 6 articles, it can be concluded that back massage can reduce first stage labor pain. Keywords: back massage, labor pain, labor pain therapy